2017
DOI: 10.1080/09593330.2017.1406537
|View full text |Cite
|
Sign up to set email alerts
|

CO2 utilization via a novel anaerobic bioprocess configuration with simulated gas mixture and real stack gas samples

Abstract: COV: coefficient of variation; Gt: gigatone; IEA: International Energy Agency; IPCC: International Panel on Climate Change; MBBR: moving bed biofilm reactor; MJ: Megajoule; UASB: upflow anaerobic sludge blanket; VFR: volumetric feeding rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Each experiment was sustained until a pseudo steady‐state condition is reached, and then, next experiment was initiated with a new gas feeding rate. Coefficient of variation (COV) less than 20% (Eqn ) was considered for pseudo steady state condition for each performance parameter such as methane formation rate, hydrogen utilization rate, methane content in the headspace 45 normalCOV0.28em=SXort×100where S is the standard deviation; X ort , average value…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each experiment was sustained until a pseudo steady‐state condition is reached, and then, next experiment was initiated with a new gas feeding rate. Coefficient of variation (COV) less than 20% (Eqn ) was considered for pseudo steady state condition for each performance parameter such as methane formation rate, hydrogen utilization rate, methane content in the headspace 45 normalCOV0.28em=SXort×100where S is the standard deviation; X ort , average value…”
Section: Methodsmentioning
confidence: 99%
“…Argon (Linde, Turkey) was utilized as the carrier gas at a flow rate of 20 mL/min. Standard gas mixture of high purity hydrogen, methane and carbon dioxide (30% H₂, 40% CH₄ and 30% CO₂) was used for GC calibration 45 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another configuration tested was hybrid systems, thus denoted because cellular biomass is present in the reactor forming granules, whereas the primary substrate is the gas injected into the reactor. This type of configuration has been tested for the conversion of H 2 :CO 2 mixtures by Daglioglu et al [150], reporting a methane production rate of 19 L/L reactor d with an H 2 injection rate of 19.2 L/L reactor d (gas injection rate of 24 L gas/L reactor d at an H 2 :CO 2 ratio of 4:1), resulting in a methane yield higher than the theoretical value of 0.25 L CH 4 /L H 2 . Microbial analysis indicated that in addition to hydrogenotrophic species, acetoclastic species were also observed in the system, although the feeding substrate was exclusively conformed by the H 2 :CO 2 mixture [151].…”
Section: Biological Conversion Of Hydrogen To Methane With Co 2 As Su...mentioning
confidence: 99%